Tatian and the Arabic Diatessaron Mark’s Ending as a Case Study - Monier, Mina (2024)
Written in late second-century Rome, Tatian’s Diatessaron is one of the earliest and most influential Gospel harmonies in history. The original text of the Diatessaron was lost, and its surviving translations suffered from alterations. However, the attention of scholarship has recently shifted toward revisiting the Arabic Diatessaron with the aim of gathering fresh evidence from its text. This study examines Mark 16 in the Arabic Diatessaron, considering an innovative approach to its text with a new body of evidence. I will study ibn at-Ṭayyib’s style of translating and understanding the Diatessaron based on his catena commentary on the four (separate) Gospels, using three newly identified witnesses that, for the first time, grant us access to the entire catena in its original recension. I will then analyze the text of Mark 16 in the Arabic Diatessaron in comparison with other editions and Gospel witnesses. I will show that the Arabic Diatessaron provides a set of readings that can be attributed to Tatian’s original work. Finally, I will provide an apparatus of the Arabic text, based (for the first time) on the entire corpus of witnesses, and a translation.
Keywords: Long Ending; Gospel of Mark; Gospels; ibn at-Ṭayyib; Diatessaron; Tatian